Software piracy among university students: Recommended solutions and a case study on students of msc of information technology, UiTM, Shah Alam / S. Sarifah Radiah Shariff and Fauziah Abdul Rahman - Shariff, S. Sarifah Radiah; Abdul Rahman, Fauziah (2004)
Copyright piracy or software piracy has been persisting problems since the dawn of Information Age. Over the past few years the public focus on copyright piracy among young technology savvy users, particularly university students. This paper will review the important highlights of software piracy among the university students, solutions being recommended by previous research as well as the issues on copyright “Fair Use” for educational and business purposes. University’s initiatives on software piracy, combination of education and technology and computer ethics as part of curriculum have been identified as possible solutions to software piracy. The recommended solution, university’s initiatives in preventing software piracy among students, was further being analysed for its effects. The analysis was based on responses from questionnaires, which were administered to 46 students of Master of Information Technology, Universiti Teknologi MARA, Shah Alam. Findings show that higher institutions play a huge role in solving the copyright issues as well a it proves that UiTM’s initiatives in the fighting the software piracy issues have positive impact on its Master of Information Technology’s students.